Morphology Of Haemonchus Species (Nematoda: Trichostrongylidae) - Abramatov Mаkhamadi Boykabulovich (Zien Journals, 2021)
The morphological features of the nematodes of the genus Haemonchus Cobbold, 1898, which is represented by two species of H. contortus Rudolphi, 1803 and H. placei Place, 1893, were studied. Based on morphological studies, the independence of two species of gemonchus, Haemonchus contortus and Haemonchus placei parasitizing in sheep and cattle, was determined.
Keywords: Nematode; Morphology; Larva; Morphometry